Globalisation And Structural Adjustment In Nigerian Public Service: A Study Of Three Government Ministries In Yobe State - Mohammed Lawan, Aminu (2021)
Globalisation has reduced the world into a small entity, and it has affected the economy of the developing nations, specifically public service. This research seeks to examine the role of structural adjustment globalisation in the public sector in Nigeria, with a particular focus on three government ministries in Yobe state. This study explores the impact of structural adjustment globalisation in public service of Yobe State, Nigeria. With the following specific objectives: i) to examine the extent to which downsizing policy of globalisation impacts job security in public service of Yobe State, Nigeria. ii) To evaluate how the monetisation policy of globalisation impacts working conditions in public service of Yobe State, Nigeria. iii) To analyse how the casualisation policy of globalisation affects the job security in public service of Yobe State, Nigeria. iv) To examine the impacts of neoliberal globalisation on public service of Yobe state, Nigeria. It was built on neoliberal and contingent worker theories as a framework for analysis. This study employed qualitative research methodology, with in-depth interviews administered on 15 public servants purposively selected from three ministries in Yobe state as participants. The data were coded and analysed using thematic analysis with the support of NVivo 12 software. The research findings show implementing the structural adjustment globalisation can be conducted in a manner that shall not hurt the public servants in developing countries like Nigeria